Effects of the environment on species richness and composition of vascular plants in Manaslu Conservation Area and Sagarmatha region of Nepalese Himalaya - Rai, S. K.; Sharma, S.; Shrestha, K. K.; Gajurel, J. P.; Devkota, S.; Nobis, M. P.; Scheidegger, C. (Banko Janakari, 2016)
This study analyzed how the environmental conditions constrained the species richness and composition in the four river valleys of Central Nepal i.e. two from Manaslu Conservation Area (MCA) and two from Sagarmatha region. Topographical, bioclimatic and measured variables were used to analyze their effects on the vascular plant diversity along elevation and land use gradients. Altogether, 148 plots were established at five elevation levels between 2,200 m and 3,800 m above the mean sea level. Four land use types namely crop field, meadow, exploited forest and natural forest were sampled at each elevation level. Altogether, 790 species of vascular plants belonging to 114 families were recorded; Asteraceae had the highest number of species (84) followed by Rosaceae (52) and Poaceae (50). Explorative data analysis of species composition by canonical correspondence analysis (CCA) showed that the topographical variables explained the composition better than both the bioclimatic set of variables and the logger data. However, all groups of variables revealed significant effects on species composition. Generalized Linear Model (GLM) also revealed significant effects of elevation, land-use types, slope angle, aspect, temperature and precipitation on species richness. Banko Janakari A Journal of Forestry Information for Nepal Vol. 26, No. 1, Page: 3-16, 2016